A conserved KLF-autophagy pathway modulates nematode lifespan and mammalian age-associated vascular dysfunction - Paishiun N. Hsieh (Nature Portfolio, 2017)
KLF family transcription factors (KLFs) regulate many cellular processes, including proliferation, survival and stress responses. Here, the authors position KLFs as important regulators of autophagy and lifespan in C. elegans, a role that may extend to the modulation of age-associated vascular phenotypes in mammals.